2008
DOI: 10.1136/jnnp.2007.130583
|View full text |Cite
|
Sign up to set email alerts
|

Attempted and completed suicides after subthalamic nucleus stimulation for Parkinson's disease

Abstract: A higher than expected frequency of suicide has been reported among patients undergoing subthalamic nucleus deep brain stimulation (STN DBS) for advanced Parkinson's disease (PD). We conducted a retrospective survey of 200 patients with PD who underwent STN DBS. Two patients (1%) committed suicide and four (2%) attempted suicide, despite clear motor improvements. Suicidal patients did not differ from non-suicidal patients with respect to age, disease duration or preoperative depressive and cognitive status. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 23 publications
1
64
0
9
Order By: Relevance
“…88 A higher-than-expected frequency of suicide has also been reported among patients undergoing STN DBS for advanced PD. 89 In a prospective study of 20 patients during the 2 years after surgery, however, Houeto et al 90 showed that provided patients with PD are rigorously selected for neurosurgery, STN stimulation improves mood, anxiety, and quality of life. The procedure does not result in severe permanent psychiatric disorders or modify patients' personalities, and it does not improve social function.…”
Section: Cognitive Side Effects Of Dbsmentioning
confidence: 99%
“…88 A higher-than-expected frequency of suicide has also been reported among patients undergoing STN DBS for advanced PD. 89 In a prospective study of 20 patients during the 2 years after surgery, however, Houeto et al 90 showed that provided patients with PD are rigorously selected for neurosurgery, STN stimulation improves mood, anxiety, and quality of life. The procedure does not result in severe permanent psychiatric disorders or modify patients' personalities, and it does not improve social function.…”
Section: Cognitive Side Effects Of Dbsmentioning
confidence: 99%
“…Especially, a higher frequency of suicide ideation and suicides has been reported after DBS, but is still not entirely clear 55, 56. Pooled data show increased scores for depression and hypomania, but at varying degrees 54, 57.…”
Section: Device‐aided Treatment Optionsmentioning
confidence: 96%
“…After deep brain stimulation of the subthalamic nucleus, suicidal tendencies have been reported in some Parkinsonian patients (Soulas et al, 2008;Voon et al, 2008).…”
Section: Depressive Symptoms: Treatment and Prognosismentioning
confidence: 99%
“…These latter studies (Soulas et al, 2008;Voon et al, 2008) show that there might be an increased risk of suicidal behaviour in Parkinsonian patients treated with subthalamic implants, suggesting that the main risk factor for attempted and completed suicide is postsurgical depression, which on postoperative follow-up should be adequately diagnosed and treated with anti-depressant drugs.…”
Section: Depressive Symptoms: Treatment and Prognosismentioning
confidence: 99%
See 1 more Smart Citation